Kesiapan Sumber Daya Manusia Kesehatan dalam Menghadapi Masyarakat Ekonomi Asean (MEA) - Aragar Putri (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2017)
Health Human Resources are the backbone of the health care efforts face an increase in the number and proportion of productive age population and the elderly in the future mendatang.Terutama in the face of the Asean Economic Community. Health Human Resources, aims to produce human resources that develop and update health science and technology in the field of health promotion. HRH able to identify and formulate solutions development and management of health human resources through research, develop / improve the performance of professional indicated by the sharpness of the analysis of health problems, formulate and advocate for programs and health policies for the development and management of health human resources.